Certain Verbs Are Syntactically Explicit Quantifiers - Anna Szabolcsi (The Baltic International Yearbook of Cognition, Logic and Communication, 2010)
Quantification over individuals, times, and worlds can in principle be made explicit in the syntax of the object language, or left to the semantics and spelled out in the meta-language. The traditional view is that quantification over individuals is syntactically explicit, whereas quantification over times and worlds is not. But a growing body of literature proposes a uniform treatment. This paper examines the scopal interaction of aspectual raising verbs (begin), modals (can), and intensional raising verbs (threaten) with quantificational subjects in Shupamem, Dutch, and English. It appears that aspectual raising verbs and at least modals may undergo the same kind of overt or covert scope-changing operations as nominal quantifiers; the case of intensional raising verbs is less clear. Scope interaction is thus shown to be a new potential diagnostic of object-linguistic quantification, and the similarity in the scope behavior of nominal and verbal quantifiers supports the grammatical plausibility of ontological symmetry, explored in Schlenker (2006). References Ben-Shalom, D. 1996. Semantic Trees. Ph.D. thesis, UCLA. Bittner, M. 1993. Case, Scope, and Binding. Dordrecht: Reidel. Cresswell, M. 1990. Entities and Indices. Dordrecht: Kluwer. Cresti, D. 1995. ‘Extraction and reconstruction’. Natural Language Semantics 3: 79–122. http://dx.doi.org/10.1007/BF01252885 Curry, B. H. & Feys, R. 1958. Combinatory Logic I. Dordrecht: North-Holland. Dowty, D. R. 1988. ‘Type raising, functional composition, and non-constituent conjunction’. In Richard T. Oehrle, Emmon W. Bach & Deirdre Wheeler (eds.) ‘Categorial Grammars and Natural Language Structures’, 153–197. Dordrecht: Reidel. Fox, D. 2002. ‘TOn Logical Form’. In Randall Hendrick (ed.) ‘Minimalist Syntax’, 82–124. Oxford: Blackwell. Gallin, D. 1975. Intensional and higher-order modal logic: with applications to Montague semantics. North Holland Pub. Co.; American Elsevier Pub. Co., Amsterdam: New York. Groenendijk, J. & Stokhof, M. 1984. The Semantics of Questions and the Pragmatics of Answers. Ph.D. thesis, University of Amsterdam. Heim, I. 1992. ‘Presupposition projection and the semantics of attitude reports’. Journal of Semantics 9: 183–221. http://dx.doi.org/10.1093/jos/9.3.183 Heim, I. 2001. ‘Features of Pronouns in Semantics and Morphology’. Ms., Universität Tübingen. Heim, I. & Kratzer, A. 1998. Semantics in Generative Grammar. Oxford: Blackwell. Herman, H. 1993. Studied Flexibility: Categories and Types in Syntax and Semantics. Ph.D. thesis, University of Amsterdam. Hintikka, J. 1962. Knowledge and Belief. Ithaca, NY: Cornell UP. Homer, V. 2009. ‘Epistemic modals: high ma non troppo’. In ‘Proceedings of NELS 40’, . Iatridou, S. 1994. ‘On the contribution of conditional then’. Natural Language Semantics 2: 171–199. http://dx.doi.org/10.1007/BF01256742 Jacobson, P. 1999. ‘Towards a variable-free semantics’. Linguistics and Philosophy 22: 117-184. http://dx.doi.org/10.1023/A:1005464228727 Karttunen, L. 1977. ‘The syntax and semantics of questions’. Linguistics and Philosophy 1: 1–44. Kusumoto, K. 2005. ‘On the quantification over times in natural language’. Natural Language Semantics 13: 317–357. http://dx.doi.org/10.1007/s11050-005-4537-6 Lasnik, H. 1999. ‘Chains of arguments’. In Samuel Epstein & Norbert Hornstein (eds.) ‘Working Minimalism’, 189–217. Cambridge, MA: The MIT Press. Lassiter, D. 2011. Measurement and Modality: The Scalar Basis of Modal Semantics. Ph.D. thesis, New York University. Lechner, W. 2006. ‘An interpretive effect of head movement’. In Mara Frascarelli (ed.) ‘Phases of Interpretation’, 45–71. Berlin: Mounton de Gruyter. Lechner, W. 2007. ‘Interpretive Effects Of Head Movement’. Ms., http://ling.auf.net/lingBuzz/000178 (accessed January 15, 2011). Mascarenhas, S. 2010. ‘Causing-to-have vs. Having-for: The Syntax of Double-object Get’. Ms., New York University. May, R. 1985. Logical Form: Its Structure and Derivation. Cambridge, MA: The MIT Press. Montague, R. 1974. ‘The proper treatment of quantification in ordinary English’. In R. Thomason (ed.) ‘Formal Philosophy: Selected Papers of Richard Montague’, 247–271. New Haven and London: Yale University Press. Nchare, A. L. 2011. The Grammar of Shupamem. Ph.D. thesis, New York University. Partee, B. 1973. ‘Some structural analogies between tenses and pronouns in English’. The Journal of Philosophy 70, no. 18: 601–609. http://dx.doi.org/10.2307/2025024 Percus, O. 2000. ‘Constraints on Some Other Variables in Syntax’. Natural Language Semantics 8, no. 3: 173–229. http://dx.doi.org/10.1023/A:1011298526791 Percus, O. & Sauerland, U. 2003. ‘On the LFs of attitude reports’. In Proceedings of Sinn und Bedeutung. Perlmutter, D. 1970. ‘The two verbs begin’. In R. Thomason (ed.) ‘Readings in English Transformational Grammar’, 107–119. Waltham, MA: Blaisdell. Polinsky, M. 2008. ‘Real And Apparent Long-distance Agreement In Subject-to-subject Raising Constructions’. Lecture at the Annual Meeting of the German Linguistic Society, Bamberg. Quine, W. V. O. 1960. ‘Variables explained away’. Proceedings of the American Philosophical Society 104: 343–347. Schlenker, P. 1999. Propositional Attitudes and Indexicality (A Cross-Linguistic Approach). Ph.D. thesis, MIT. Schlenker, P. 2004. ‘Sequence phenomena and double access readings generalized’. In J. Lacarme & J. Guéron (eds.) ‘The Syntax of Time’, 555–597. Cambridge, MA: The MIT Press. Schlenker, P. 2006. ‘Ontological symmetry in language’. Mind and Language 21: 504–539. http://dx.doi.org/10.1111/j.1468-0017.2006.00288.x Stechow, A. von. 2004. ‘Binding by verbs: tense, person, and mood under attitudes’. In H. Lohnstein & S. Trissler (eds.) ‘The Syntax and Semantics of the Left Periphery’, 431–488. Berlin: de Gruyter. Stechow, A. von. 2008. ‘Tenses, Modals, and Attitudes as Verbal Quantifiers’. Ms., ESSLLI Hamburg. Stechow, A. von. 2009. ‘Syntax and semantics: an overview’. To appear in: Maienborn, Claudia et al. (eds.), Semantics: An International Handbook of Natural Language Meaning. Berlin: Mouton de Gruyter. Steedman, M. 1988. ‘Combinators and Grammars’. In R. Oehrle, E. Bach & D. Wheeler (eds.) ‘Categorical Grammars and Natural Language Structures’, 417–442. Dordrecht. Steedman, M. 2000. The Syntactic Process. Cambridge, MA: The MIT Press. Stowell, T. 1995a. ‘The Phrase Structure of Tense’. In J. Rooryck & L. Zaring (eds.) ‘Phrase Structure and Lexicon’, 277–291. Dordrecht: Kluwer. Stowell, T. 1995b. ‘What Do the Present and Past Tenses Mean?’ In P. Bertinetto et. al. (ed.) ‘Temporal Reference, Aspect, and Actionality. Vol. 1: Semantics and Syntactic Perspectives’, 381–396. Torino: Rosenberg and Sellier. Szabó, Z. G. 2011. ‘Bare quantifiers’. Philosophical Review 120: 247–283. Szabolcsi, A. 1987. ‘Bound variables in syntax (are there any?)’. In J. Groenendijk et. al. (ed.) ‘Sixth Amsterdam Colloquium’, 331–351. Amsterdam: Institute for Language,Logic, and Information. Szabolcsi, A. 1992. ‘Combinatory grammar and projection from the lexicon’. In I. A. Sag & A. Szabolcsi (eds.) ‘Lexical Matters. CSLI Lecture Notes 24’, 241–269. Stanford, CSLI Publications. Szabolcsi, A. 2009a. ‘Overt nominative subjects in infinitival complements cross-linguistically’. http://www.nyu.edu/gsas/dept/lingu/nyuwpl/. Szabolcsi, A. 2009b. ‘Overt nominative subjects in infinitival complements in Hungarian’. In M. den Dikken & V. Robert (eds.) ‘Approaches to Hungarian 11’, 251–276. Amsterdam: John Benjamins. Szabolcsi, A. 2010. Quantification. Cambridge: Cambridge University Press. Yanovich, I. 2009b. ‘How Much Expressive Power Is Needed For Natural Language Temporal Indexicality?’ In L. D. Beklemishev & R. de Quieroz (eds.) ‘Proceedings of Logic,Language, Information and Computation’, 293–309. 18th International Workshop, WoLLIC 2011, Philadelphia, PA, USA. Dordrecht: Springer.